Managing capital flows: The case of Indonesia - Ira Setiati Titiheruw; Raymond Atje (Asian Development Bank Institute (ADBI), 2008)
This paper describes Indonesia's experiences in managing foreign capital flows after the 1997 financial crisis. It highlights several differences in types and magnitude of capital flows from the pre-crisis period and reviews the determinants of capital flows including government policy and regulatory framework to respond to the influx of capital flows. The paper concludes that the country's policy still focuses on ways to mobilize foreign (and domestic) capital to return in order to finance the resource gap by maintaining macroeconomic stability, improving the investment climate and enhancing prudential supervision of foreign capital flow utilization, particularly by the banking and private sectors.
Keywords: E52; F21; F41; 330; Kapitalimport; Kapitalverkehrspolitik; Indonesien